Identification of Candidate Olfactory Genes in the Antennal Transcriptome of the Stink Bug Halyomorpha halys - Sun, Dongdong; Huang, Yuan; Qin, Zhenjie; Zhan, Haixia; Zhang, Jinping; Liu, Yang; Yang, Shiyong (Frontiers in Physiology, 2020)
The brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), is a serious agricultural and urban pest that has become an invasive species in many parts of the world. Olfaction plays an indispensable role in regulating insect behaviors, such as host plants location, partners searching, and avoidance of predators. In this study, we sequenced and analyzed the antennal transcriptomes of both male and female adults of H. halys to better understand the olfactory mechanisms in this species. A total of 241 candidate chemosensory genes were identified, including 138 odorant receptors (ORs), 24 ionotropic receptors (IRs), 15 gustatory receptor (GRs), 44 odorant binding proteins (OBPs), 17 chemosensory proteins (CSPs) and three sensory neuron membrane proteins (SNMPs). The results of semi-quantitative reverse transcription PCR assays showed that some HhalOBP and HhalCSP genes have tissue-specific and sex-biased expression patterns. Our results provide an insight into the molecular mechanisms of the olfactory system in H. halys and identify potential novel targets for pest control strategies.